Enhancing bacterial production of a recombinant cetuximab-Fab by partial humanization and its utility for drug conjugation - Sim, Dae Won; Song, Jinsue; Kim, Ji Hun; Lee, Jun Kyoung; Chung, Da Yoon; Jo, Ku Sung; Kim, Chan Gil; Seo, Min Duk; Kang, Ho Chul; Paeng, Jin Chul; Kim, Young Pil; Won, Hyung Sik (Process Biochemistry, 2018)
Cetuximab is a murine-human chimeric monoclonal antibody (mAb) that is clinically used to treat epidermal growth factor receptor (EGFR)-positive cancers. As antibody fragment engineering has emerged as an economic alternative to mAb drugs via bacterial production, we have previously generated FM318, a recombinant Fab adopted from cetuximab. Here, in an effort to facilitate industrial development, we searched for useful mutations that could increase its production yields. Amino acid substitutions were selected to resemble the humanized sequence to avoid unexpectedly raising immunogenic problems by the mutations. As a result, FM329, which accommodates L3Q/L4 M mutations in the light chain and S15G/Q16G in the heavy chain Fd, showed a high production yield in a fed-batch operation, reaching approximately 3.5 times FM318 productivity, with its structure and EGFR-binding affinity being maintained. Additionally, for a potential application to antibody-drug conjugates, a cytotoxic agent, DM1 was successfully linked to FM329 with an average drug-to-antibody ratio of 1.4. The conjugate showed dramatically increased anticancer activity with retention of EGFR-binding affinity. Collectively, we suggest that the partially humanized recombinant cetuximab Fab, FM329, and its DM1 conjugate would serve as promising platforms to develop an economic alternative to cetuximab and/or an improved drug candidate for a potent anti-cancer therapy.
Keywords: Antibody engineering; Antibody fragment; Antibody-drug conjugates; Bacterial production; Cetuximab; Humanization; Antibody engineering; Antibody fragments; Antibody-drug conjugates; Bacterial production; Cetuximab Fab; Humanization